Socio-demographic, clinical, and health-related factors associated with breast reconstruction – A nationwide cohort study. Issue 5 (October 2015) - Bodilsen, Anne; Christensen, Søren; Christiansen, Peer; Damsgaard, Tine E.; Zachariae, Robert; Jensen, Anders B.
Abstract We collected registry- and questionnaire-based data on socio-economic and health status, tumor- and treatment-related variables, and explored associations with receipt of reconstruction and information about treatment options in a nationwide cohort of Danish women, treated for primary breast cancer. A total of 594 women were available for analysis, 240 (40%) of these received reconstruction. Multivariate analyses showed that receipt of reconstruction was associated with 1) younger age at time of primary surgery (<36 years: OR = 10.04, [3.80–26.50], p < 0.001 and 36–49 years: OR = 2.48, [1.73–3.56], p < 0.001, compared to 50–60 year olds), 2) having received radiotherapy (OR = 0.57, [0.40–0.81], p = 0.002), 3) high income (Second quartile: OR = 1.74, [1.05–2.90], p = 0.033 and fourth quartile: OR = 2.18, [1.31–3.62], p = 0.003, compared with the lowest income quartile), and 4) ethnicity other than Danish (OR = 6.32, [1.58–25.36], p = 0.009). Health-related factors at the time of primary surgery (physical functioning, body mass index, smoking, use of alcohol, and comorbidity) were not associated with reconstruction. Odds of having received information about the option of reconstruction decreased by 8% per year of age in the multivariate analysis (OR = 0.92, [0.87–0.97], p = 0.003). In conclusion, younger age and not having been treated with radiotherapy was independently associated with reconstruction. In addition, higher income was also found to be associated with reconstruction despite free and equal access to reconstruction and healthcare in Denmark. Healthrelated factors were not associated with the use of reconstruction following mastectomy. Our findings underscore the need for physicians to ensure optimal level of information and accessibility to reconstruction for all women regardless of age, treatment, and socio-economic status.